2002
DOI: 10.1186/1297-9686-34-5-581
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for lactation traits of milking ewes: protein content and composition, fat, somatic cells and individual laboratory cheese yield

Abstract: -The effects of some environmental variation factors and the genetic parameters for total milk traits (fat content, protein content, casein content, serum protein content, lactation mean of individual laboratory cheese yield (LILCY), lactation mean of somatic cell count (LSCC), and milk yield) were estimated from the records of 1 111 Churra ewes. Genetic parameters were estimated by multivariate REML. Heritability for fat content was low (0.10) as is usually found in the Churra breed. Heritabilities for protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 39 publications
2
4
0
1
Order By: Relevance
“…The ten VOC that had the highest estimated heritability among the VOC that were tentatively identified or unidentified are in Tables 3 and 4, respectively. The results confirm that several individual spectrometry peaks are characterized by heritability estimates of the same magnitude as those for milk yield, some milk quality traits [30, 31] and also some technological parameters [32]. …”
Section: Resultssupporting
confidence: 71%
“…The ten VOC that had the highest estimated heritability among the VOC that were tentatively identified or unidentified are in Tables 3 and 4, respectively. The results confirm that several individual spectrometry peaks are characterized by heritability estimates of the same magnitude as those for milk yield, some milk quality traits [30, 31] and also some technological parameters [32]. …”
Section: Resultssupporting
confidence: 71%
“…Moreover, there is a need to confirm whether the same physiological mechanism explains the effects detected on PP and FP, and why some of our analyses were not as conclusive for the FP trait as they are for the PP trait. On this regard, it should be taken into account that in dairy sheep, milk FP shows, in general, a lower heritability than milk PP [52] , [53] . Hence, it is possible that the lower heritability for this trait indicates that there are additional non-genetic factors that are not being controlled in the YD estimation model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the laboratory simulation process of individual cheese manufacturing followed in this study is not completely comparable to that of the dairy industry. As other authors have suggested, micro-cheese factoring can determine an overestimation of the actual cheese yield due to the limited amount of milk used (Puledda et al, 2017;Othmane et al, 2002b;Jaramillo et al, 2008). In any case, ILCY is the most commonly used parameter for the calculation of the individual laboratory cheese yield, and many different studies have used it as a good proxy trait to assess the cheese-making ability of dairy species (Othmane et al, 2002b,c;Cellesi et al, 2019).…”
Section: Phenotype Basic Statistics and Genotype Quality Filteringmentioning
confidence: 99%